2013
DOI: 10.1038/bjc.2013.656
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of vaginal and abdominal radical trachelectomy for early-stage cervical cancer: preliminary results of a multi-center research in China

Abstract: Background:There are limited data comparing the prognosis and fertility outcomes of the patients with early cervical cancer treated by trans-vaginal radical trachelectomy (VRT) or abdominal radical trachelectomy (ART).The objective of this study was to compare the surgical and pathologic characteristics, the prognosis and fertility outcomes of the patients treated by VRT or ART.Methods:Matched-case study based on a prospectively maintained database of patients underwent radical trachelectomy in 10 centres of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 16 publications
3
85
0
5
Order By: Relevance
“…It is well known that the extent of the excised tissue is determined by the tumour's size, location and endocervical margin. ART is preferable when the median diameter of the tumour is larger because some authors believe that the oncological outcomes of tumours P2 cm in size tend to be better following ART groups than other surgical approaches [6,22,23]. Additionally, a growing number of authors employing ART preferred a 10-mm negative margin, which might be due to large tumour size [17,19,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the extent of the excised tissue is determined by the tumour's size, location and endocervical margin. ART is preferable when the median diameter of the tumour is larger because some authors believe that the oncological outcomes of tumours P2 cm in size tend to be better following ART groups than other surgical approaches [6,22,23]. Additionally, a growing number of authors employing ART preferred a 10-mm negative margin, which might be due to large tumour size [17,19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to VRT, ART produces better oncological outcomes, has a shorter learning curve and can technically be performed by any trained gynaecologic oncologists. However, fertility outcomes of ART were unfavourable compared with VRT [6]. In 2003, Lee [7] introduced the first laparoscopic radical trachelectomy (LRT).…”
Section: Introductionmentioning
confidence: 99%
“…The decision for lymphodissection depends on LVSI in this case as well. In stage IA2 trachelectomy is the only option in order to preserve fertility (6).…”
Section: • Surgery As Primary Treatment For Cervical Cancermentioning
confidence: 99%
“…It is known that radical vaginal trachelectomy has better reproductive outcomes than abdominal trachelectomy [3,[6][7][8][9]. The mechanistic reasons for this superiority remain unclear, but less invasive approaches preserving much more tissue and nerves around the cervix may contribute.…”
Section: Commentsmentioning
confidence: 99%
“…Patients with FIGO stage Ia2-Ib1 with small tumor size (less than 2 cm in diameter) without retroperitoneal lymph node metastases have been likely to undergo this operation, and the oncologic outcomes have been reported to be satisfactory, comparable with radical hysterectomy [3][4][5]. However, the reproductive outcomes of this operation appear insufficient, and some reports indicated that radical vaginal trachelectomy, rather than abdominal trachelectomy, shows more favorable reproductive outcomes [3,[6][7][8][9], while the oncologic outcomes of vaginal trachelectomy appeared to be inferior to those of the abdominal procedure, especially in patients with tumors larger than 2 cm [8,[10][11][12]. The precise cause of the relatively poor reproductive outcomes of abdominal radical trachelectomy remains unclear, but it is possible that disruption of autonomic nerves that innervate the uterine Objectives: Nerve-sparing techniques to avoid bladder dysfunction in abdominal radical hysterectomy have been established during the past two decades, and they have been applied to radical trachelectomy.…”
Section: Introductionmentioning
confidence: 99%